2015
DOI: 10.1111/mpp.12220
|View full text |Cite
|
Sign up to set email alerts
|

Rice stripe tenuivirus p2 may recruit or manipulate nucleolar functions through an interaction with fibrillarin to promote virus systemic movement

Abstract: Rice stripe virus (RSV) is the type species of the genus Tenuivirus and represents a major viral pathogen affecting rice production in East Asia. In this study, RSV p2 was fused to yellow fluorescent protein (p2-YFP) and expressed in epidermal cells of Nicotiana benthamiana. p2-YFP fluorescence was found to move to the nucleolus initially, but to leave the nucleolus for the cytoplasm forming numerous distinct bright spots there at later time points. A bimolecular fluorescence complementation (BiFC) assay showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 53 publications
(90 reference statements)
2
44
1
Order By: Relevance
“…With the exception of Rubisco, which remained enriched in band 1, the most abundant host protein precipitating with anti-P20 IgG was a nucleolar protein, fibrillarin, which was detected in band 2 in three independent experiments (Table 1). Fibrillarin is known to interact with viral MPs and is important for long-distance trafficking of several RNA viruses (Kim et al, 2007;Taliansky et al, 2010;Semashko et al, 2012;Zheng et al, 2015). The LC-MS/MS results were confirmed by immunoblot analysis, revealing the presence of P20 and fibrillarin in the P20 co-IP complex in the HV coinfected tissues (Figures 4C and 4D).…”
Section: Host Factors Immunoprecipitated With P20 Proteinsupporting
confidence: 62%
See 1 more Smart Citation
“…With the exception of Rubisco, which remained enriched in band 1, the most abundant host protein precipitating with anti-P20 IgG was a nucleolar protein, fibrillarin, which was detected in band 2 in three independent experiments (Table 1). Fibrillarin is known to interact with viral MPs and is important for long-distance trafficking of several RNA viruses (Kim et al, 2007;Taliansky et al, 2010;Semashko et al, 2012;Zheng et al, 2015). The LC-MS/MS results were confirmed by immunoblot analysis, revealing the presence of P20 and fibrillarin in the P20 co-IP complex in the HV coinfected tissues (Figures 4C and 4D).…”
Section: Host Factors Immunoprecipitated With P20 Proteinsupporting
confidence: 62%
“…Fibrillarin is required for rRNA processing (Barneche et al, 2000;Sáez-Vasquez et al, 2004) and is a nucleolar-localized RBP required for systemic infection of GRV (Kim et al, 2007;Canetta et al, 2008), Potato leafroll virus (Haupt et al, 2005), and Rice stripe tenuivirus (Zheng et al, 2015). Nucleolar colocalization of fibrillarin and P20 protein (Figure 7), along with detection of fibrillarin, P20 protein, and satBaMV RNA in co-IP complexes (Figures 4 and 6) but not in the fibrillarin RNAi transgenic line (Supplemental Figure 5 and Supplemental Tables 1 and 2), is consistent with the evidence for interaction of fibrillarin with satBaMV-P20 RNP complexes ( Figure 4E, Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…). Different VPs, such as satBaMV P20 (Chang et al ., ), RSV P2 (Zheng et al ., ), hordei‐like TGB1s (Lukhovitskaya et al ., ; Semashko et al ., ), BBSV p7a (Wang et al ., ), PVA VPg (Rajamaki & Valkonen, ) and GRV ORF3 (Kim et al ., ), traffic to the nucleolus via interactions with the importin α/β or other pathway. These diverse VPs interact with Fib2 in the nucleolus and initiate the formation of viral RNP (vRNP) complex intermediates that are transported to the cytoplasm (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the RSV infects not only rice plants but also maize, wheat, oat, foxtail millet, weeds and Arabidopsis [7,15,22]. Until now, several host factors have been identified that interact with RSV proteins or RNA, and those factors are thought to be recruited or manipulated by RSV and used to complete its life cycle [6,16,33]. Notably, the RSV nonstructural protein p2, a viral silencing suppressor, can bind to a rice host protein that is homologous to the suppressor of gene silencing in Arabidopsis (AtSGS3) [6].…”
Section: Introductionmentioning
confidence: 99%